Analysis of the April 13, 2021 bolide off the coast of Florida and Grand Bahama Island. (20th January 2022) - Hughes, Ashley; Sankar, Ramanakumar; Davis, Kathryn E.; Palotai, Csaba; Free, Dwayne L.
Abstract: In this paper, we examine the trajectory, orbital, and radiometric characteristics of the bolide event occurring off the coast of southern Florida and the Grand Bahama Island on April 13, 2021. An object measuring about 1.3 m in diameter entered the atmosphere at approximately 02:16:40 UTC at a velocity of 16 km s −1 . It took an almost due north course between Florida and Grand Bahama Island, terminating in the Atlantic Ocean. No fragments have been recovered up to the date of submission of this paper. We used a fragmentation model to infer the internal structure of the object. We found that the best fit to the light curve and height of the peak energy deposition is with a weak stony meteor, with a density of about 2000 kg m −3, that disrupted and fragmented quickly, over a time interval of 1.5 s, or over a distance of about 11 km in altitude, between 45 and 34 km. We find that the impactor had a preatmospheric mass of 2.5 ± 0.5 t, resulting in a diameter of about 1.34 ± 0.09 m. We performed a backward integration of the trajectory to determine an orbit and found that the impacting object was a Jupiter family comet with a semimajor axis of about 3.6 AU, and an inclination of 9°, which is consistent with our analysis from the fragmentation model. We could not find a suitable candidate for a parent body.